Development Of Qiraah Teaching Materials Based On Nusantara Folklores In Arabic Language Education Faculty Of Language And Literature, Makassar State University - Enung Mariah S; Sarah Noviyanti Latuconsina; Arief Fiddienika (Seminar Nasional LP2M UNM, 2022)
Abstrak. This research is in the form of development research in the form of developing teaching materials for qiraah courses based on archipelago folklore. The purpose of this research is to develop teaching materials for courses with the nuances of Indonesian folklore that students are expected to be able to apply the values of local wisdom contained in Indonesian folklore. This study uses the R&D research method of developing a 4-D learning device model from Thiagarajan, Semmel, and Semmel (1974). The stages are in the form of limitation stages, design stages, development stages, and deployment stages. The results of this study are the development of qiraah teaching materials based on Indonesian folklore that are suitable for use with material expert validation after revision getting a score of 90% and from learning experts after revision getting 91% results. Kata Kunci: RnD, Qiraah Teaching Materials, Folklores